Influence of macromedia flash based on computer animation media to improving student learning outcomes in the Haloalkane sub-discussion - Dhani, Dwi Suci Rahma; Asep Wahyu Nugraha (ARKA INSTITUTE, 2022)
During learning students face difficulties in understanding abstract chemistry topics. Currently there is no appropriate media to be applied in the learning process in order to increase students' abilities. Therefore, a study was conducted using macromedia flash based on computer animation to improve learning outcomes in Madrasah Aliyah Negeri (MAN) 2 Medan Model schools in the Haloalkana sub discussion. This study aims to determine the effect of macromedia flash based on computer animation media on student learning outcomes in the haloalkane sub-discussion and to determine the correlation between the responses given by students to macromedia flash based on computer animation media in the haloalkane sub-discussion. The population of these two samples was taken using random sampling technique, namely class XII IPA 9 as the experimental class and class XII IPA 10 as the control class. The type of this research is quasi-experimental using the pretest and posttest models. Data collection was carried out using multiple choice instruments and response questionnaires. Based on the results of the study, it was found that there was an increase in student learning outcomes between the experimental class and the control class after the implementation of computer animation-based macromedia flash in the Haloalkana sub-discussion at MAN 2 Model Medan and there was a relationship between the responses given by students to computer animation based macromedia flash media in improvement of learning outcomes.